Gendered Leadership Dynamics and Female Leadership: Underrepresentation of Women in Leadership Positions in Azerbaijani Higher Education Institutions - Hasanli, Sara (ADA University, 2024)
This study aimed to initiate a discourse regarding the underrepresentation of women in academic leadership positions in Azerbaijani higher education institutions (HEIs). The review in the thesis critically analyzed the global scientific community and the theoretical frameworks that were used to investigate factors that may have influenced or hindered women's representation in academic leadership positions. Following a qualitative methodology, the data was gathered via semi-structured interviews with 12 individuals, comprising high-ranking individuals within the university hierarchy, encompassing positions such as Heads of Laboratories and Divisions, Faculty Deans, Department Heads, and other individuals from both genders who hold leadership posts at the university. A thematic analysis unveiled a number of significant findings. Initially, the results of this study provided insights into multiple facets of the gender imbalance present in academic leadership positions at Azerbaijani HEIs. The academic community's perspectives on academic leadership and the essential attributes of an effective leader in academia are exposed through the discourse surrounding academic leadership. Perceived differences in leadership styles between males and females were also revealed. The factors that contribute to the underrepresentation of women in leadership positions were determined and categorized as external, institutional, and individual-level factors considering the responses of participants. Although there was consistency with the findings of previous research conducted in other contexts, the cultural element was a distinguishing characteristic of the experiences of female leaders in Azerbaijan. The significance of fostering gender diversity in leadership positions to improve the performance of organizations and establish a more inclusive atmosphere within academic institutions was determined. The results of the study emphasized the necessity for structured interventions, gender mainstreaming initiatives, and institutional reform to foster gender diversity and equality in Azerbaijani higher education institutions. Large-scale research would be conducted to make the topic more scrutinized and/or investigated, to establish cause-and-effect relationships, to test hypotheses, and to determine the opinions, attitudes, and practices of a large population, to reach generalizability, which in turn could contribute to the progression of women into positions of academic leadership and cultivate inclusive environments.
Keywords: Women in academia -- Leadership -- Azerbaijan; Azerbaijan -- Education -- Gender issues; Women executives -- Education -- Azerbaijan; Azerbaijan -- Higher education -- Gender diversity; Education